Transition metal-based materials for oxygen electrocatalysis - Wang, Jiarui (Nanyang Technological University, 2023)
With the continuous development of human society, the energy demand is also increasing. Researchers have put much effort into developing clean and renewable energy, such as solar energy, wind energy, tidal energy, nuclear energy, biomass energy, hydrogen energy, etc. Developing energy storage and conversion technologies that can efficiently utilize these renewable and clean energies is of great significance for solving the current problems of energy shortage and environmental pollution. Oxygen reduction and evolution reactions (ORR and OER) are the core reaction processes of many important energy storages or conversion technologies. However, the slow kinetics of the oxygen redox reaction limited the energy efficiency. In addition, the heavy reliance on noble metal-based electrocatalysts also restricted the development of related devices. Therefore, the development of high-performance, low-cost ORR, and OER electrocatalysts have become a major challenge. At the same time, understanding the mechanism of electrocatalytic reaction from the atomic level is the prerequisite for the rational design of efficient electrocatalysts. Now, special attention has been given to transition metal-based materials. By controlling the composition of Ir-Cu nanoparticles via a facile chemical reduction method and electrochemical post-leaching procedures, the influence of Ir-Cu bimetallic NPs with various atomic ratios on the ORR performance has been studied. The improved activity is ascribed to the increased active surface area via Cu dealloying and enhanced electronic structures. Second, the entropy stabilization effect on the OER performance of spinel type high entropy oxide (HEO) was examined. The electrochemical OER performance, as well as the long-term durability, have been studied for Zn(CrMnFeCoNi)2O4. It is found that the formation of MOxHy increases the surface entropy from original spinel HEOs, which results in a significant improvement in the catalysis performance. In addition, the construction of HEOs with the exclusion of a single element leads to decreased Abstract ii electrochemical performance, further indicating the positive effect of high entropy on the OER catalysis. Third, by analysing the surface reconstruction process of spinel LixCo3–xO4 during a long period OER process, a feasible theoretical approach is established to predict the degree of surface reconstruction. In addition, a series of spinel ZnAl1.5FexNiyCo0.5-x-yO4 (x = 0, 0.125, 0.375, y = 0, 0.125) have been prepared, which confirms and validates a rational structure-reconstruction relationship for spinel oxides. The established fundamentals for studying surface reconstruction may also be extended to other types of TMOs.